Scalar struggles: the selectivity of development governance in Southern Mexico - Lehmann, Rosa; Jenss, Alke (Latin American research review, 2022)
So-called development projects in rural Mexico are heavily contested. Changes in institutional design have had little effect in mediating the exclusivity of the political decision-making processes defining such projects. Why, and how, has the Mexican state been able to maintain a developmentalist agenda, despite growing pressures to incorporate participatory development institutions and consult Indigenous peoples about development projects? This article introduces the geographic concept of scale and the concept of the state’s heterogeneous selectivities into debates on participation to study the politics of development projects. It analyzes the potential and existing obstacles to political participation for Indigenous networks and activists in the corresponding planning processes across institutional scales, examining protest against wind energy development in the state of Oaxaca and the project of “rural cities” in the state of Chiapas. Rather than two separate cases for comparison, both examples represent different planning processes involving the same heterogeneous state and the same promise of progress., ResumenLos llamados proyectos de desarrollo en el México rural son muy cuestionados. Los cambios en el diseño institucional han tenido poco efecto en la mediación de la exclusividad de los procesos de decisión política que definen dichos proyectos. ¿Por qué y cómo ha podido el Estado mexicano mantener una agenda desarrollista, a pesar de las crecientes presiones para incorporar instituciones de desarrollo participativo y consultar a los pueblos indígenas sobre los proyectos de desarrollo? Introducimos el concepto geográfico de escala y el concepto de selectividad heterogénea del Estado en los debates sobre participación política, para estudiar los procesos políticos alrededor de esos proyectos. Analizamos los obstáculos potenciales y existentes para la participación política de redes y activistas indígenas en los procesos de planificación correspondientes a través de diferentes escalas institucionales, basándonos en la protesta contra el desarrollo de la energía eólica en el estado de Oaxaca, y el proyecto de “ciudades rurales” en Chiapas. Más que dos casos distintos en comparación, ambos ejemplos representan diferentes procesos de planificación que involucran al mismo estado heterogéneo, y la misma promesa de progreso.
Gesehen am 20.12.2022
Keywords: Mexiko